2023
DOI: 10.1167/iovs.64.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Long Noncoding RNA NEAT1/miR-320a/HIF-1α Competitive Endogenous RNA Regulatory Network in Diabetic Retinopathy

Abstract: Purpose To determine the mechanism that long noncoding RNA NEAT1 (lncNEAT1)/miR-320a competitive endogenous RNA (ceRNA) network regulates hypoxia-inducible factor–1α (HIF-1α) in ARPE-19 cells and its potential role in diabetic retinopathy (DR). Methods ARPE-19 cells were cultured in a normal or high-glucose (HG) medium, and cell migration, invasion, and permeability were detected by scratch, transwell, and FITC-dextran staining assays. LncNEAT1, HIF-1α, ZO-1, occludin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…HIF-1α plays an unfavorable role as a central stimulator of angiogenesis in PDR, as evidenced by the fact that hypoxia induces the up-regulation of HIF-1α, which in turn increases the expression of VEGF and promotes the formation of retinal blood vessels [ 41 ]. Recent studies have shown that HIF-1α overexpression in diabetic rats enhances the invasion, migra tion, and permeability of ARPE-19 cells, exacerbating retinal damage [ 42 ]. It is also worth mentioning that patients with DKD and anemia are at a significantly higher risk of developing PDR, with some combination of the two.…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1α plays an unfavorable role as a central stimulator of angiogenesis in PDR, as evidenced by the fact that hypoxia induces the up-regulation of HIF-1α, which in turn increases the expression of VEGF and promotes the formation of retinal blood vessels [ 41 ]. Recent studies have shown that HIF-1α overexpression in diabetic rats enhances the invasion, migra tion, and permeability of ARPE-19 cells, exacerbating retinal damage [ 42 ]. It is also worth mentioning that patients with DKD and anemia are at a significantly higher risk of developing PDR, with some combination of the two.…”
Section: Introductionmentioning
confidence: 99%